Trump stored and refused to return documents, felony indictment says - Euronews; Associated Press (euronews, 2023)
Donald Trump improperly stored in his Florida estate sensitive documents on nuclear capabilities, repeatedly enlisted aides and lawyers to help him hide records demanded by investigators and cavalierly showed off a Pentagon “plan of attack” and classified map, according to a felony indictment.
Keywords: 2023-06 June